(untitled) (Linguostylistic Studies, 2014)
This article deals with the investigation of phraseological units which appear in Lesya Ukrainka’s private and public correspondence. Extensive attention is devoted to the way in which ideological, social, national and cultural factors are reflected in the language found in these sources, and the manner in which it manifests the potent influence which Lesya Ukrainka exerted intellectually and culturally. In this paper, consideration has been given to the very concept of the «phraseological unit», as well as to the distribution of these units. The usage of phraseological units in the letters of the poetess has been analyzed. Different types of phraseological unit transformations in Lesya Ukrainka’s language style have been identified. Phraseological units as she utilizes them reflect a language-related world view in national images, of which the internal semantics symbolizes and expresses the evaluation of feelings, the state of nature, the phenomena of the inner world, and the writer’s creative imagination. Her usage of phraseological units had an influence on the development of the language, on the establishment of norms, and on the formation of national traditions involving the culture and language of individuals. During the process of analysing the language of Lesya Ukrainka’s letters, specific features have been identified, and esthetic patterns have been singled out which in a general sense are characteristic features of words as they occur in artistic language. Key words: language personality, epistolary, phraseological unit, dialect, style. References